Analisis Strategi Digital Marketing dalam Pemasaran Album Fisik Musik K-Pop di Indonesia - Aprilia Sari; Yuni Firayanti; Rosadi Rosadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The study analyzes digital marketing strategies in the promotion of physical K-pop music albums in Indonesia. The scope of the study is on the strategies used by the music industry to increase the visibility and sales of physical K-pop albums. The study also examines the benefits of purchasing physical albums and the reasons behind fans’ consumptive behavior. The study was using descriptive qualitative method, with in-depth interviews conducted with 23 respondents (3 sellers and 20 buyers) in Pontianak. Data were collected through documentation, observations and interviews. The results indicate that digital marketing involves the use of social media, streaming sites, and music applications to interact with fans and expand the market. Factors influencing purchasing decisions include digital promotions and fan community interactions. This study provides insights that support the growth of digital marketing strategies for the K-pop music industry in Indonesia and enriches the understanding of the importance of digital marketing in a global context, adapted to the local market.